Pengaruh Variasi Kadar CaCO3 terhadap Pertumbuhan Fase Superkonduktor BPSCCO–2212 Menggunakan Metode Pencampuran Basah - Suprihatin; Rianggi Wahyuni Pratiwi; Simon Sembiring; Roniyus Marjunus (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
This research was conducted to determine the effect of CaCO3 levels on the formation of superconducting phase BPSCCO - 2212 by calculating the level of purity of the phases formed and looking at the microstructure. The variation of CaCO3 was 0.95, 1.00, 1.05 and 1.10 mole using the wet mixing method. The samples were calcined at 800 ° C for 10 hours, and sintered at 820 ° C for 20 hours. Synthesized samples were characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The XRD’s chacterization results show that the level of purity of the formed phases increases with increasing Ca levels with maximum point at BPSCCO-2212/1.10 mole. The highest volume fraction was 79,06% in the BPSCCO-2212/1.10 sample. While the lowest volume fraction was 72.10% in the BPSCCO-2212/0.95 sample. Meanwhile, the highest degree of orientation was 20.59% at BPSCCO-2212/0.95. The lowest degree of orientation was 8.46% at BPSCCO-2212/1.10. SEM’s chacterization results show of all samples have been oriented altought not perfect yet and have relatively little space between slabs (voids).